Cloning, purification, crystallization and preliminary structural studies of penicillin V acylase from Bacillus subtilis - Rathinaswamy, P.; Pundle, A. V.; Prabhune, Asmita; SivaRaman, H.; Brannigan, James A.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology Communications, 2005)
{Penicillin acylase proteins are amidohydrolase enzymes that cleave penicillins at the amide bond connecting the side chain to their beta-lactam nucleus. An unannotated protein from Bacillus subtilis has been expressed in Escherichia coli, purified and confirmed to possess penicillin V acylase activity. The protein was crystallized using the hanging-drop vapour-diffusion method from a solution containing 4 M sodium formate in 100 mM Tris-HCl buffer pH 8.2. Diffraction data were collected under cryogenic conditions to a spacing of 2.5 A. The crystals belonged to the orthorhombic space group C222(1), with unit-cell parameters a = 111.0